2022
DOI: 10.1155/2022/9105068
|View full text |Cite
|
Sign up to set email alerts
|

Dietary γ-Aminobutyric Acid (GABA) Promotes Growth and Resistance to Vibrio alginolyticus in Whiteleg Shrimp Litopenaeus vannamei

Abstract: An 8-week feeding trial was conducted to evaluate the effects of dietary γ-aminobutyric acid (GABA) on growth performance, immune response, and disease resistance for juvenile whiteleg shrimp, Litopenaeus vannamei. Five isonitrogenous diets were formulated by supplementing 0 (CON), 50 (GABA50), 100 (GABA100), and 300 (GABA300) mg of GABA and 4 g of oxytetracycline (OTC) per kilogram of diet. A total of 225 juvenile whiteleg shrimp with an initial weight of 2.97 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
3
7
0
Order By: Relevance
“…In a trial by Farris et al [ 13 ], juvenile olive flounder supplemented with GABA (237 mg/kg) demonstrated improved growth, digestive enzyme activities and innate immunity when challenged with the pathogen Streptococcus iniae. Similar beneficial results were found by Bae et al [ 12 ] in whiteleg shrimp ( Litopenaeus vannamei ) supplied with a supplementation of GABA at 100 mg/kg including bacterial resistance against Vibrio alginolyticus . Thus far, investigations into the effects of GABA in the diet of teleost fish have largely focused on its ability to modulate physiological pathways connected to growth and immune responses under ideal abiotic environmental parameters.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a trial by Farris et al [ 13 ], juvenile olive flounder supplemented with GABA (237 mg/kg) demonstrated improved growth, digestive enzyme activities and innate immunity when challenged with the pathogen Streptococcus iniae. Similar beneficial results were found by Bae et al [ 12 ] in whiteleg shrimp ( Litopenaeus vannamei ) supplied with a supplementation of GABA at 100 mg/kg including bacterial resistance against Vibrio alginolyticus . Thus far, investigations into the effects of GABA in the diet of teleost fish have largely focused on its ability to modulate physiological pathways connected to growth and immune responses under ideal abiotic environmental parameters.…”
Section: Introductionsupporting
confidence: 86%
“…Thus GABA A and GABA B are differentially involved in multiple functions of neuronal circuits in the OB of fish [ 3 ]. In recent years, a great number of studies have been performed to assess the physiological effects that GABA supplementation may have in aquatic species important to the aquaculture industry [ 9 , 10 , 11 , 12 , 13 ]. Although GABA has been utilized for quite some time to induce settling and metamorphosis in abalone [ 14 , 15 ], it has been recently demonstrated to have significant contributions to the growth, feeding behavior, appetite, digestion and immune status of crustaceans and teleost fish [ 6 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the analysis of the current study, significantly higher SOD levels were obtained in the experimental groups to which GABA was added. It was found that GABA decreased oxidative stress and increased the activity of antioxidant enzymes in fish, as found in humans, rats, broilers, hens, and pigs, as well as similar to those found in fish and shellfish [15,[20][21][22][23][24][25][26][27][28][29]45]. The results of the present study indicate that dietary GABA can attenuate stress in fish due to high stocking density, which is in agreement with results found in the case of the antioxidant enzyme SOD in Roman hens exposed to heat stress [44], the glutathione (GSH) enzyme in largemouth bass fish exposed to ammonia stress and in turbot fed a high soybean meal diet [52,53].…”
Section: Discussionsupporting
confidence: 71%
“…After homogenization, the above mixture was made into a paste using 300 mL of water, and the resulting paste was changed to stable sticks using a meat grinder. The pellets were dehumidified for 36 h and then kept at 4 • C until consumption [26]. Finally, the biochemical status of each diet was analyzed using the standard AOAC [27] protocol.…”
Section: Diet Preparation and Experimental Designmentioning
confidence: 99%